Factors That Affect Vitamin K Injection To Newborn By Midwives At Bukittinggi Area on 2017 - Felina, Mutia; Marlina, Marlina (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
Vitamin K is a fat-soluble vitamin that has an important role in activating substances that play a role in blood clotting, including substances known as prothrombin and clotting factors. The purpose of this research is to know the knowledge factor of midwife toward vitamin K in the newborn with midwifery in the prevention of vitamin K deficiency in the newborn in Bukitinggi city. This type of research is cross-sectional, and this research is done in Bukittinggi City Year 2017. Sampling technique with Random Sampling or randomly. The research will be carried out in the Working Area of Bukittinggi City in 2017. The population and sample in this study are all midwives who have BPM in Bukittinggi City with a sample size of 21 midwives. Data analysis with chi-square showed that there was no correlation between midwife knowledge on vitamin K administration in BBL with the working period and availability of midwife in preventing vitamin K deficiency on BBL with p = 0,0001 (p> 0,05). It is recommended for health workers in Kota Bukittinggi to improve the standard services of Midwifery, especially to newborns.